Microsatellite Diversity and Restriction Enzyme-based Polymorphisms of MHC Loci in Some Native Turkish Goats - Mehmet Aslan; Eymen Demir; Taki Karslı (Journal of Agricultural Sciences)
Playing a key role in immunity and autoimmunity, Major Histocompatibility Complex (MHC) contains microsatellite regions and polymorphisms associated with resistance to several diseases and thermo-physiologic characteristics in farm animals. This study aims to reveal genetic diversity in four native Turkish goat populations via MHC related gene regions including MHC-linked microsatellite markers (BF1, BM1818, BM1258, SMHCC1 and DYMS1) and MHC Class II-DRB gene. A total of 120 unrelated animals belonging to Hair (HAI), Honamlı (HNM), Kabakulak (KBK) and Norduz (NRD) from different representative populations in Antalya and Van provinces were sampled and genotyped for molecular analysis. Based on MHC-linked microsatellite markers, number of alleles ranged from 8.20 (NRD) to 8.80 (HAI and KBK) across studied goat populations. Observed heterozygosity was between 0.68 (NRD) and 0.80 (KBK), whereas expected heterozygosity ranged from 0.74 (NRD) to 0.82 (KBK) in native Turkish goats. Inbreeding coefficients were 0.04, 0.13, -0.01 and 0.09 for HAI, HNM, KBK and NRD populations, respectively. A 284 bp length PCR products belonging to MHC Class II-DRB gene region were digested separately with PstI, TaqI, BsaHI and AluI restriction endonucleases to assess polymorphism status together with Hardy-Weinberg equilibrium in studied goat populations. P allele frequency ranged from 0.73 (KBK) to 0.95 (NRD), while p allele frequency was between 0.05 (NRD) and 0.27 (KBK) in PstI polymorphism. The highest and lowest frequency of T allele were detected in HNM (0.80) and KBK (0.49), respectively, whereas frequency of t allele was between 0.20 (HNM) and 0.51 (KBK) in TaqI polymorphism. G and A allele frequency were between 0.16 (HNM) - 0.39 (HAI) and 0.84 (HNM) – 0.61 (HAI), respectively in BsaHI polymorphism, while three different genotypes and two alleles, which were different from results reported in the literature, were observed in AluI polymorphism. In this study, high genetic diversity and low inbreeding were detected in native Turkish goats according to MHC-linked microsatellite markers. Similarly, native Turkish goats hold enough polymorphisms in MHC Class II-DRB gene which gives opportunity to support selection strategies against tuberculosis and heat stress in the future.